Efektivitas E-Government dalam Penerapan Program E-Kelurahan - Widya Cancer Rusnita; Desna Aromatica; Roni Ekha Putera (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2023)
E-Kelurahan is a web-based application used for document publishing at Kelurahan. This study stems from the many problems of the implementation of e-Kelurahan in Padang City including low user access, problem access, and e-Kelurahan limitations in online service delivery. The study aims to analyze the implementation of the e-kelurahan program in Padang City with more complex components. The analysis is carried out on technical site development, internal government, and client perspectives. The research method used descriptive qualitative. The theory is the Six Dimensional Assessment Tool (6DAT) for analyzing the Effectiveness of e-Government. These six dimensions are used as variable Security systems, Integrated Database Development, Intra-Agency Hierarchical Integration, Inter-Agency Lateral Coordination, Interactive Public Access, and Transparency of Government Structure and Process. According to the findings of this study, the implementation of the e-Kelurahan in Padang City is still ineffective. Even though the e-Kelurahan application is being improved to be more secure, it has an integrated database that is credible and up to date, and lateral relationships through joint partnerships are running smoothly, on the other hand, user experience is less concerned. however communication facilities to internal parties that are not provided to the public, in the lack of transparency of processes and structures, in the lack of interactivity of e-Kelurahan, and most importantly, in the lack of efficient access. It can be concluded, both in terms of applications, the organizers and the public are still in the transition stage to transform to digital.